Four years of clinical experience with the efficacy of Pulpotec® as a root canal dressing for the management and control of odontogenic pain: A prospective randomized clinical trial - Faraj, Bestoon Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2013)
Background: The choice of methods and materials for the relief of preoperative symptom and control of inter-appointment flare-up remains an important consideration in endodontic therapy. Aim: The objectives of this study was to discover clinically the influence of pulpotec (Produits Dentaires S.A., Switzerland) on the incidence of inter-appointment flare-up, with a view to advance the resolution of pain and/or swelling in patients presenting for emergency root canal treatment. Materials and Methods: Pulpotec paste was used as an intracanal medicament in multi-appointment root canal treatment in 860 teeth (510 symptomatic and 350 asymptomatic) belonging to 860 patients from February 2008 to March 2012. The follow-up visit was scheduled, and the incidence and severity of inter-appointment pain was recorded at different time periods (8, 24, and 48 h, 3 days, and 1 week after the treatment) on simple descriptive pain intensity scale. Results: The incidence of intense pain was 10 (1.16%) and 6 (0.69%) of the treatment cases at 24 and 48 h, respectively. Moderate pain was described only by 137 patients within the 24 h–3 days time interval after treatment. Conclusion: Pulpotec intracanal dressing is beneficial in rapid resolution of pain and/or swelling in emergency root canal treatment and in controlling postoperative pain in multi-appointment root canal treatment.
Keywords: Odontogenic pain; pulpotec; root canal dressing